The Effect of Profitability on the Stock Price: Empirical Study from PT. Bank Danamon Indonesia - J. Jumria; Agussalim Rahman (Golden Ratio of Finance Management, 2026)
This study aims to analyze the influence of Return on Assets and Return on Equity, which reflect profitability ratios, on PT's stock price. Bank Danamon Indonesia Tbk. The research method used is descriptive quantitative research, an approach that measures phenomena objectively using numerical data. The data analysis method used descriptive quantitative analysis to calculate and analyze each research variable. Multiple regression analysis was used to assess the relationship between Return on Assets, Return on Equity, and stock prices. The results of the calculations and analyses show the influence of ROA and ROE on PT's stock price. Bank Danamon Indonesia Tbk. regression equation obtained: Y = 483,650 + 93,318 X1 + 905,423 X2. The results of the simultaneous significance test indicate that Fhit = 5.42 < Ftab = 19.00, so it is concluded that Return on Assets and Return on Equity have no significant effect on stock prices. Partial significance test X1 is t hit 0.488 < t tab 2.353 means Return on Assets has a positive effect, but not significant on stock prices. Meanwhile, the significance test of X2 found t = 3.270 > ttab = 2.353, indicating that Return on Equity has a positive effect and significantly impacts stock prices. Therefore, it is recommended to continue improving profitability ratios so that total asset and capital management can make a positive, significant contribution to PT's stock price. Bank Danamon Indonesia Tbk.